2020
DOI: 10.1007/s11694-020-00657-0
|View full text |Cite
|
Sign up to set email alerts
|

Study on optimization of extraction technique of pericarp essential oil in Litsea Cubeba (Lour) Pers

Abstract: Litsea cubeba is an important aromatic oil plant. Litsea cubeba pericarp essential oil has various physiological activities such as antibacterial activity, antioxidant capacity, etc., and is widely used. Its main ingredient is citral, which is the raw material for the synthesis of many precious spices. For the purpose of increasing yield, researchers have conducted many studies on the extraction of essential oil from pericarp of Litsea cubeba. But the extraction process still has room for optimization。In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Based on this study on the accumulation rule of essential oil of Litsea cubeba, the factors promoting the accumulation of essential oil of Litsea cubeba can be explored in the future. The dynamic formation and accumulation of fruit essential oils are affected by physiological and geographical changes, genetics and environmental factors (Zhang et al, 2020;Huang et al, 2021). The correlation analysis by Yuan et al (2021) showed that the essential oil content of Litsea cubeba fruit was signi cantly negatively correlated with the longitude of origin, and mean temperature in July, negatively correlated with annual rainfall and positively correlated with altitude.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this study on the accumulation rule of essential oil of Litsea cubeba, the factors promoting the accumulation of essential oil of Litsea cubeba can be explored in the future. The dynamic formation and accumulation of fruit essential oils are affected by physiological and geographical changes, genetics and environmental factors (Zhang et al, 2020;Huang et al, 2021). The correlation analysis by Yuan et al (2021) showed that the essential oil content of Litsea cubeba fruit was signi cantly negatively correlated with the longitude of origin, and mean temperature in July, negatively correlated with annual rainfall and positively correlated with altitude.…”
Section: Discussionmentioning
confidence: 99%
“…The hotspot mainly focuses on the seedling propagation and cultivation technology of Litsea cubeba (Wei et al, 2017), the extraction, processing and application of Litsea cubeba essential oil, and the application of Litsea cubeba in medicine. Studies on the essential oil of Litsea cubeba, including optimization of the extraction process of Litsea cubeba essential oil (Huang et al, 2021), analysis of essential oil components from different parts of Litsea cubeba (Ho et al, 2021;Wang et al, 2010), and rich biological characteristics of Litsea cubeba essential oil such as antioxidant activity (Jae- Kwan et al, 2005) and antibacterial or antifungal activity (Hu et al, 2019;Wu et al, 2019). There are also some studies on the application of Litsea cubeba essential oil, including the potential application of Litsea cubeba essential oil in the cosmetic industry (Huang et al, 2013) and the possibility of Litsea cubeba essential oil as an e cient and environmentally friendly antifungal fumigant (Li et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, LCEO extracted from other organs is considered to be lower in quality, in terms of citral content and bioactivity, than that from fruit (Su & Ho, 2016). The yield of fruit essential oil is related to the fruit maturity; the mature fruit is ideal for essential oil extraction as it yields more than immature or overripe fruits (Chen, 2001;Huang et al, 2021). Currently, the most common method for LCEO extraction is traditional steam distillation that uses water as the solvent, that is, hydrodistillation.…”
Section: Extraction Of Lceomentioning
confidence: 99%
“…The EO was extracted by steam distillation (feed to liquid ratio = 1:10) for 150 min, and then the EO was separated out. The EOC was calculated as described by Huang et al (2020) [30]. The fruits were collected from 750 trees in this survey, and the TFW and TDW were calculated from fresh and dry weight values of 1000 de-stemmed L. cubeba fruits.…”
Section: Fruit Characteristicsmentioning
confidence: 99%